2008
DOI: 10.4137/bmi.s590
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependent Gene Expression Changes in the Liver of Mice Treated with Benzene

Abstract: Benzene is used as a general purpose solvent. Benzene metabolism starts from phenol and ends with p-benzoquinone and o-benzoquinone. Liver injury inducted by benzene still remains a toxicologic problem. Tumor related genes and immune responsive genes have been studied in patients suffering from benzene exposure. However, gene expression profiles and pathways related to its hepatotoxicity are not known. This study reports the results obtained in the liver of BALB/C mice (SLC, Inc., Japan) administered 0.05 ml/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Our gene expression study (29) also confirmed that downregulation of CYP2610 and CYP4A10 genes after benzene treatment accounts for biochemical and histopathological changes in BALB/c mice. We also observed that circadian rhythm affects benzeneinduced lipid peroxidation (30).…”
Section: Discussionsupporting
confidence: 81%
“…Our gene expression study (29) also confirmed that downregulation of CYP2610 and CYP4A10 genes after benzene treatment accounts for biochemical and histopathological changes in BALB/c mice. We also observed that circadian rhythm affects benzeneinduced lipid peroxidation (30).…”
Section: Discussionsupporting
confidence: 81%
“…Other experimental models have shown that exposure to trichloroethylene led to (1) protein modifications [55][56][57][58][59]; (2) synthesis of higher levels of IL-17 and IL-21 by splenocytes in trichloroethylene-treated mice [60]; (3) production of reactive oxygen species and increased nitric oxide by nitric oxide synthase in cultured human epidermal keratinocytes [61]; (4) Th1 T cell activation in MRL+/+ mice [62]; (5) inhibition of cellular apoptosis of naïve CD4+ and CD8+ T cells in MRL+/+ mice [63]; and (6) DNA hypermethylation on rat cardiac myoblasts [64]. Furthermore, other experimental studies have shown that exposure to benzene resulted in (1) decreased T cell population in wild/captive American kestrel birds [65]; (2) reduced number of CD4+/CD8+ T cells and B cells in exposed workers [66]; (3) increased reactive oxygen species and induction of DNA fragmentation in pump workers [67]; and (4) changes in gene transcription involved in apoptosis, oxidative stress, cellular cycle, and cytokine production in benzene-treated mice [68].…”
Section: Organic Solventsmentioning
confidence: 94%
“…In contrast, other reports indicate benefi cial effects of melatonin on arsenic-induced oxidative stress in the liver and kidney of Wistar rats (18). It was shown recently that expression of genes responsible for oxidative stress and detoxifi cation enzymes is altered by benzene in mice (40). Genes corresponding to the circadian rhythm were also affected by benzene (40).…”
Section: Discussionmentioning
confidence: 60%
“…It was shown recently that expression of genes responsible for oxidative stress and detoxifi cation enzymes is altered by benzene in mice (40). Genes corresponding to the circadian rhythm were also affected by benzene (40). Several reports have confi rmed that antioxidative effects of melatonin are caused by at least two different mechanisms, which might, however, be interdependent (41).…”
Section: Discussionmentioning
confidence: 99%